(3GdWQjb Gdi GMJQGa (BSQL SERVERs - (3gGfj(B, (3YHO GdfHjs ((3GdbGgQI(B:s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B,s, 2004)
(3ebOeI Yf bhGYO GdHjGfGJ(B- (3LedI (BDATA SELECT- (3GSJNOeGJ eJbOeI ddCeQ(BSELECT- (3GfTGA YfGUQ bGYOI GdHjGfGJ(B- (3GdJYGed eY GdHjGfGJ(B- (3GfTGA YfGUQ HjGfGJ CNQi(B- (3GdJMce aj UdGMjGJ GdeSJNOejf(B- (3GdELQGAGJ GdCMOGK(B- (3JWHjb Ydi bGYOI GdHjGfGJ (BSQL(3HGSJNOGe (Bvisual basic .s
Keywords: SQL SERVER; (3GdEYdGe GdCdjs; (3GdHQeLjGJs; (3GdMGShHs